Evaluación Financiera a la Cooperativa de Ahorro y Crédito Cariamanga Ltda., del Cantón Calvas, períodos 2019-2020 - Jumbo Narváez, Catherine del Cisne (2023)
The Curriculum Integration work "Financial Evaluation of Cooperativa de Ahorro y Crédito Cariamanga Ltda., Calvas Canton, periods 2019-2020, was developed in order to accomplish the stated objectives and seek alternatives that contribute to the economic development of the cooperative, to establish a real diagnosis to strength the financial and economic situation. In order to accomplish the stated objectives, it was necessary to evaluate the structure of the Financial Statements, which allowed the execution of the vertical analysis of each study period, measuring the degree of participation of each account that intervenes, with respect to the financial structure of the assets in its largest participation is represented by Credit Portfolio in 2019 with a value of $2,845,905.88 equivalent to 74.23% and in 2020 $3,490,196.63 with representation of 65.39%; Within the group of liabilities, the obligations with the public are presented in 2019 with a value of $3,298,224.78 equivalent to 86.03% and in 2020 with $4,775,522.27 that represents 89.47% which are derived from the term and savings deposits made by the partners in the financial entity, which must be managed in the best way; the Equity is adequate to support current and future operations, considering an adequate structure; With respect to the economic structure in income, the interests and discounts earned represent $342,765.85, which represents 91.28% in 2019 and a value of $524,961.06 equivalent to 92.17% in 2020, due to the fact that there is an efficient profit from the interests collected for the credits granted, which is the main intermediation activity. In addition, the horizontal analysis was carried out on the Financial Statements of the cooperative, establishing the financial movements and variations such as an increase or decrease in accounts, determining an increase in: the Credit Portfolio in 2019 obtained a value of $2,845,905.88 while in 2020 was $3,490,196.63, giving a difference of $644,290.75, which represents 22.64%, since in this year the values of microcredits to expire increased; in 2019 , the Obligations with the public registered an amount of $3,298,224.78 and in 2020 a value of $4,775,522.27 with a difference of $177,297.49 equivalent to 44.79% and the Equity for 2019 a value of $311,066.39 and in 2020 of $387,734.40 with a difference of $76,668.01 which is equivalent to 24.65% as a result of the good management of the policies that the cooperative has; Regarding to the total incomes, they increased to $371.569,44 in 2019 while in 2020 a value of $567.469.85 with a difference of $195,873.41 equivalent to 52,71. 5 Likewise, the financial indicators established by the Superintendencia de Economía Popular y Solidaria (SEPS) were applied, which allowed establishing the patrimonial solvency with a total for the year 2019 of 63,32% and for 2020 the 67,21% giving a variation of 0,90%. which can solve your estate correctly for future decisions; productive assets with a value of 79,01% while for 2020 of 81,96%% giving a variation of 2,95%, the total portfolio delinquency was obtained 0.63% in 2019 and 1.29% in 2020 with a variation of 0.67% reflecting the recovery of the microcredit portfolio that does not accrue interest, liquidity obtains 17.73% in 2019 and 51.78% in 2020 with the variation of 34, 05% significant value that allows to respond to shortterm obligations. Finally, an evaluation report has been developed with a clear and comprehensive language in which the results of the analysis carried out were presented, specifically the high level of liquidity and profitability of the company, so that the negative aspects do not affect the financial operations and can make appropriate decisions that help managers and administrators to improve the performance of the activities of the savings and credit cooperative.